Complication and surgical site infection for salvage surgery in head and neck cancer after chemoradiotherapy and bioradiotherapy. Issue 5 (October 2017) - Suzuki, Hidenori; Hanai, Nobuhiro; Nishikawa, Daisuke; Fukuda, Yujiro; Hasegawa, Yasuhisa
Abstract: Objective: We aimed to investigate the complications, surgical site infection (SSI), and survival in salvage surgery without free-flap reconstruction for patients with head and neck squamous cell carcinoma who were treated by platinum-based chemoradiotherapy (Plat-CRT) or cetuximab-based bioradiotherapy (Cet-BRT). Methods: Thirty-three patients treated by Plat-CRT and six treated by Cet-BRT had salvage surgery. We categorized postoperative complications according to the Clavien–Dindo classification and SSI according to the wound grading scale. Overall survival calculated by Kaplan–Meier method. Results: Patients with Cet-BRT were significantly associated with the presence of SSI ( P  < 0.01) and grades IIIb–V of the Clavien–Dindo classification ( P  < 0.01) compared with those with Plat-CRT. Patients with Cet-BRT had a significantly lower overall survival than those with Plat-CRT ( P  < 0.05). Conclusion: We demonstrated that patients with Cet-BRT were significantly more associated with the presence of SSI and grades IIIb–V in the Clavien–Dindo classification than those with CRT.